Mutational spectrum of dystrophinopathies in Singapore: Insights for genetic diagnosis and precision therapy. Issue 2 (13th May 2019) - Tomar, Swati; Moorthy, Vikaesh; Sethi, Raman; Chai, Josiah; Low, Poh Sim; Hong, Stacey Tay Kiat; Lai, Poh San
Abstract: Duchenne and Becker muscular dystrophies (DMD/BMD) are X‐linked recessive disorders caused by mutations in the DMD gene. Emerging therapies targeting patients with specific mutations are now becoming a reality for many of these patients. Precise molecular diagnosis is essential to facilitate the identification of possible new treatments for patients in the local context. In this study, we screened 145 dystrophinopathic patients in Singapore and assessed their molecular status for eligibility to current emerging genetic therapies. Overall, 140 (96.5%) of all patients harbored pathogenic DMD mutations comprising 95 exonic deletions (65.5%), 14 exonic duplications (9.7%), and 31 pathogenic small mutations (21.4%). Nonsense and frameshift mutations constitute 83.9% of all the small mutations. We found 71% (103/145) of all Singaporean dystrophinopathy patients to be theoretically amenable for exon skipping, either through skipping of single (53.1%) or multiple exons (17.9%). This approach is applicable to 81.1% (77/95) of patients carrying deletions and 83.9% (26/31) of those with small mutations. Eteplirsen induced skipping of exon 51 is applicable to 12.4% of local patients. Nonsense read‐through therapy was found to be applicable in another 12.4% of all patients. Mutation screening is crucial for providing insights into the underlying genetic signature of the disease in the local population and contributes toward existing information on DMD mutations in Asia and globally. This will guide future targeted drug development and clinical trial planning for this disease.